Investigation of Prospective Preschool Teachersâ€™ Beliefs about Mathematics Teaching and Learning - ErÅŸen, Zeynep Bahar; Akin, Nimet; KarakuÅŸ, Fatih (Universitas Pendidikan Indonesia, 2021)
Preschool teachers' beliefs about mathematics are crucial for qualified mathematical learning environments because children need to develop mathematical concepts based on their level of mathematical knowledge. Therefore, the purpose of this research is to determine prospective preschool teachers' beliefs about mathematics teaching and learning and to examine the effect of different variables on these beliefs. This research involved 884 prospective preschool teachers as the research sample at three state universities in Turkey. A belief Scale on mathematics teaching and learning was used as a data collection tool. The results showed that prospective teachers had positive beliefs about mathematics teaching. Moreover, there was a significant difference on prospective teachersâ€™ beliefs in accordance with grade levels. On the other hand, according to the type of prospective teachersâ€™ high school graduation, there was a significant difference in favor of prospective teachers who graduated from vocational high schools in the â€œmathematical learningâ€ and â€œnature of mathematicsâ€ sub-scales of the scale.